Drinking Water Contamination And Its Impacts On Water Quality And Public Health In Layyah, Pakistan - Liaqat Ali Waseem, Muhammad Afzal Subhani, Riaz Ul Hissan, Muhammad Shahid Maqbool, Maria Khushbakhet, Muhammad Arsalan, Ammara Anis (Migration Letters, 2024)
The aim of the current study is to examine the impact of contaminated drinking water on human health and water quality in Layyah, Punjab (Pakistan). This research utilized both primary and secondary data to measure the impact of contaminated water on water quality and public health during 2016-2022. The data was collected from Public Health Authority (Punjab) and through a. structured questionnaire from 152 households by using snowball sampling technique. The current study applied Ordinary Least Square Method and Inverse [1]Distance Weighting (IDW) Analysis through GIS software to observe the relationship among selected variables. The findings of this study show that contaminated water had a significant negative impact on public health which creates such problems as hepatitis, asthma, kidney problems, cardiovascular complications, and waterborne diseases specifically cholera and typhoid. The study is intended to provide a comprehensive guide to address these issues, particularly emphasizing health-related concerns arising from uneven water consumption practices and the presence of pollutants in the local water supply. Further, this study also suggests the strategies to rectify the water crisis, ensuring access to clean and safe drinking water for the residents of this area.